The impact of aids in nursing practice: a public health problem - Gir, Elucir; Prado, Marinésia A.; Canini, Silvia R.M.S.; Hayashida, Miyeko (Brazilian Journal of Sexually Transmitted Diseases, 2005)
Introduction: the possibility of occupational transmission of the Hepatitis B virus has been recognized a lot earlier than the case of the AcquiredImmunodeficiency Virus (HIV). Nevertheless, as a result of the appearance of aids, nursing workers became worried about their practice and the useof preventive measures. Although the Hepatitis B and C viruses offer greater risk of seroconversion, the risk of HIV infection is still causing greaterimpact among health workers. Nowadays, seroconversions for HIV, HBV and HCV are considered a global public health problem. Objective:iden-tify the impact of aids in nursing practice. Methods:This is a descriptive study, involving nursing auxiliaries at a Public School Hospital. Results: out of a total of 100 professionals, 82% mentioned changes in their professional practice, 68.4% of which referred to adherence to standard precau-tions, while 60.5% say this change resulted from the fear of infection. Although the professionals point out the practical behavioral change throughadherence to standard precautions, we perceive the need to deliver further information to the workers about all protection measures. We know thatgarments as an isolated measure do not guarantee a decrease in the occupational risk of getting pathogens borne by blood and other body fluids. Conclusion: we highlight the need to implement educational actions that are able to contribute to nursing professionals’ increased comprehension ofthe occupational risk of HBV, HCV and HIV.